2021
DOI: 10.1093/ofid/ofab267
|View full text |Cite
|
Sign up to set email alerts
|

High Cure Rates for Hepatitis C Virus Genotype 6 in Advanced Liver Fibrosis With 12 Weeks Sofosbuvir and Daclatasvir: The Vietnam SEARCH Study

Abstract: Background Genotype 6 is the most genetically diverse lineage of hepatitis C virus (HCV), and predominates in Vietnam. It can be treated with sofosbuvir with daclatasvir (SOF/DCV), the lowest costing treatment combination globally. In regional guidelines, longer treatment durations of SOF/DCV (24 weeks) are recommended for cirrhotic individuals, compared with other pangenotypic regimens (12 weeks), based on sparse data. Early on-treatment virological response may offer means of reducing lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Of 455 patients screened, 52 were enrolled and 1 subsequently withdrew ( Figure 2 ). Most exclusions were on account of either a FibroScan score of >7.1 kPa (with cirrhotic patients enrolled into a parallel study; Flower et al, 2021 ), or ineligible genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Of 455 patients screened, 52 were enrolled and 1 subsequently withdrew ( Figure 2 ). Most exclusions were on account of either a FibroScan score of >7.1 kPa (with cirrhotic patients enrolled into a parallel study; Flower et al, 2021 ), or ineligible genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Of 455 patients screened, 52 were enrolled and one subsequently withdrew (figure 2). Most exclusions were on account of a either a fibroscan score of >7.1kPa (with cirrhotic patients enrolled into a parallel study 35 ),or ineligible genotype.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Michaluk et al demonstrated that SVR attained in HCV GT4 mono-infected patients did not differ significantly from HCV/HIV co-infected patients, underlining the safety and effectiveness of current DAA therapy for HCV/HIV co-infected patients [ 23 ]. A study by Flower et al demonstrated no contribution of RAS to treatment outcomes in a cohort in Vietnam where HCV GT6 was predominant [ 24 ]. Although the existence of RAS (NS5a region) at the baseline did not influence the attainment of SVR in our analysis, we need large sample size studies to draw firm confirmations on the impact of BL-RAS on treatment response in HCV GT6 infected patients.…”
Section: Discussionmentioning
confidence: 99%